Acupuncture in the emergency department (ACUITY): Results from a BraveNet multi-center feasibility randomized controlled trial - Jeffery A. Dusek; Gene A. Kallenberg; Alan B. Storrow; Robert M. Hughes; Christopher J. Coyne; David R. Vago; Arya Nielsen; Alison Karasz; Ryung S. Kim; Jessica Surdam; Tracy Segall; Kiran A. Faryar; et al. (Integrative Medicine Research)
Background: Pain plays a significant role in emergency department (ED) visits, however safe and effective nonpharmacologic options are needed. Prior studies of acupuncture in the ED reported pain reduction with minimal side effects, but most were small and single site. Methods: We conducted ACUITY, a prospectively designed multi-center feasibility RCT. Our goal was to recruit 165 adults with acute non-emergent pain ≥4 on a 0–10-point scale at three EDs affiliated with BraveNet Practice Based Research Network. At baseline and 45–60 min later (post), participants self-assessed their pain and anxiety using a 0–10 rating scale. The primary feasibility outcome was recruitment of participants, whereas secondary outcomes were retention, and participant/provider acceptability. Results: From May 3, 2021, to September 24, 2022, 632 eligible individuals were approached and 165 enrolled (165/632: 26.1 %), meeting our recruitment goal. Notably, 42.4 % of enrollees were Black/African American, 42.4 % were White/Caucasian, and 13.9 % were Hispanic/Latino. Participants were randomized to Acupuncture (n = 83) or Usual care (n = 82), of which 151 (91.5 %) and 128 (77.6 %) provided pain and anxiety scores at post-treatment and 1-week respectively. Acupuncture was rated acceptable to participants and providers. Mean pain ratings (pre-to-post) were 7.4 (2.2) to 4.8 (2.8) for acupuncture and 7.1 (2.3) to 6.4 (2.5) for usual care. Mean anxiety ratings (pre-to-post) were 4.5 (3.4) to 2.5 (2.6) for acupuncture and 4.1 (3.4) to 3.5 (3.2) for usual care. Conclusion: Successful completion of ACUITY indicates we have the expertise and preliminary data to conduct a future definitive, multi-center RCT. Trial registration: Clinical trials.gov: NCT04880733.